Optimizing The Use of Production Factors of Rice Mina Farming - Rozanisa, Isnaya; Wijayanti, Irene Kartika Eka; Widjojoko, Tatang; Solekan, Muhamad (JURNAL AGRIBISAINS, 2024)
Mina padi farming is an innovative farming, namely the cultivation of fish and rice in paddy fields simultaneously. Limitations of farmers in obtaining factors of production require farmers to use factors of production efficiently. Therefore it is necessary to optimize to determine the optimal combination of production factors so that farmers get the maximum profit. This study aims to calculate the profits of mina padi farming, analyze the combination of the optimal use of production factors for mina padi farming, analyze the differences in the profits of mina padi farming in the first growing season with mina padi farming in the second growing season. Sampling using simple random sampling method. The analytical method uses profit analysis, optimization analysis, and different test. The profit of mina padi farming in the first planting season is Rp6,115,340.00 and in the second planting season is Rp6,487,589.00. The optimization model estimation result showed that the use of farming resource was not yet optimal. The use of production factors is not optimal as indicated by the excessive use of inputs such as capital, land, rice seeds, urea fertilizer, feed, and labor in the first growing season and the use of capital, land, ponska fertilizer, urea fertilizer, feed, and labor in the second growing season. There is a significant difference between the profits of mina padi farmers in the first growing season and the profits of mina padi farmers in the second growing season.